Effect of Combined Stress on Carbon- Epoxy Composite Curved Pipe (Journal of University of Babylon for Engineering Sciences, 2018)
The aim of this research is to study the behavior of carbon epoxy composite curve pipe under internal pressure and bending moment. Two specimens made from woven roving (Mat) carbon fiber composite pipes /epoxy composite with 50% volume fraction are used for manufacturing curved pipe. The experimental work included manufacturing pipe specimens by vacuum bag technique. Pipe specimens were having 100mm inner diameter, 490 mm length of curvature outer arc and 409 mm inner arc of curve pipe with (43 degree) and wall thickness is (4 and 3 mm). The test rig was designed and performed to study the effect of internal pressure and bending moment on the composite pipes. Also, the tensile test of the samples was done. The analytical expression solution has been accomplished to determine the strain, stress, for hoop and longitudinal direction. It is evident that the hoop stress and strain for woven roving carbon composite pipe was more than longitudinal stress and strain by almost (13%) and (18%) respectively. The maximum internal pressure in the case of internal pressure only was more than compared to the internal pressure with bending moment with almost (52%). The most critical region for stresses is found in the inner arc of the curved pipe (intrude) area while the least area for stresses was in the outer arc of the curved pipe (extrude) area.